Environmental Regulatory Standards, Energy Consumption, and Environmental Quality in Lower Middle-Income Sub-Saharan Africa: The Role of Structural Breaks - Olaoye, Olugbenga O.; Bowale, Ebenezer; Ewetan, Olabanji O. (International Journal of Energy Economics and Policy, 2025)
The primary objective of this paper is to investigate how environmental regulations in Sub-Saharan African (SSA) countries influence the nexus between energy use and environmental quality, and in particular, to ascertain the degree to which structural breaks impact the nexus. The study covered eighteen (18) middle-income (MIC) countries in sub-Saharan Africa. The research uses yearly secondary data from 1991 to 2022, and relies on the Cross Sectional Autoregressive Distributed Lag (CS-ARDL) as the estimating technique to achieve the study’s objectives. Findings indicate that structural reforms and policy shifts significantly enhance environmental quality. While economic growth positively affects environmental quality, the adverse initial impacts of regulatory changes and capital investments underscore the need for integrating climate resilience into national security strategies to sustain environmental quality in order to create a stable environment for economic activities.